2016
DOI: 10.1215/22011919-3616389
|View full text |Cite
|
Sign up to set email alerts
|

Raven, Dog, Human: Inhuman Colonialism and Unsettling Cosmologies

Abstract: As capitalism's unintended, and often unacknowledged, fallout, humans have developed sophisticated technologies to squirrel away our discards: waste is buried, burned, gasified, thrown into the ocean, and otherwise kept out-of-sight and out-of-mind. Some inhuman animals seek out and uncover our wastes. These 'trash animals' choke on, eat, defecate, are contaminated with, play games with, have sex on, and otherwise live out their lives on and in our formal and informal dumpsites. In southern Canada's sanitary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Recent work on raven behavior and ecology has demonstrated that sustained human neighborhoods often have decisive impacts on the demography and population packing of common raven [106][107][108][109] . In northern environments, raven movement, population density and seasonal ock size have been linked to the availability and concentration of anthropogenic food subsidies 110 , especially at land ll sites 111,112 , and this is also documented in Indigenous accounts, storytelling and mythology [113][114][115] . It has been noted that common raven prefer high-quality food items 89 but non-breeding ocks consistently monopolize food bonanzas related to human refuse 116 , which generally promote local avian biodiversity, notably among generalist feeders and adaptive scavengers 117 .…”
Section: Discussionmentioning
confidence: 97%
“…Recent work on raven behavior and ecology has demonstrated that sustained human neighborhoods often have decisive impacts on the demography and population packing of common raven [106][107][108][109] . In northern environments, raven movement, population density and seasonal ock size have been linked to the availability and concentration of anthropogenic food subsidies 110 , especially at land ll sites 111,112 , and this is also documented in Indigenous accounts, storytelling and mythology [113][114][115] . It has been noted that common raven prefer high-quality food items 89 but non-breeding ocks consistently monopolize food bonanzas related to human refuse 116 , which generally promote local avian biodiversity, notably among generalist feeders and adaptive scavengers 117 .…”
Section: Discussionmentioning
confidence: 97%
“…The failure of Indigenous societies to adhere to European ways of carving up the world for subordination, exploitation, and killing -for example, by not domesticating the proper animals for agriculture, or by hunting 'wild' animals for subsistence and not sport -was cited to justify the civilising mission using violence (Anderson 2004;Huggan and Tiffin 2010;Kim 2015). In this way, European settler colonialism in North America radically reconfigured the categorization of, and relationships between, the land's life-forms, dismantling and re-assembling human-nonhuman relationships within a matrix of Eurocentric-anthropocentric-androcentric power (Belcourt 2015;Zahara and Hird 2015).…”
Section: The Human and Its Others In Canadian Settler Colonialismmentioning
confidence: 99%
“…Ethnographic studies of everyday waste practices remind scholars and researchers that definitions of waste are often culturally specific and produced through specific regimes of meaning or knowledge. Zahara and Hird (2015), for instance, explore how western and Inuit cosmologies around waste and 'trash animals' diverge in ways that marginalize Inuit ways of knowing (see too Douny, 2007). These understandings of diverse practices of understanding and engaging with waste make clear that universal framings of waste need to take seriously specific contexts, dynamics, and histories (see Drackner, 2005;Furniss, 2017;Winegar, 2016;Machado-Borges, 2017).…”
Section: Southern Theory and The Geographies Of Wastementioning
confidence: 99%